Quantitative analysis of MRI‐guided radiotherapy treatment process time for tumor real‐time gating efficiency. Issue 11 (22nd October 2020) - Placidi, Lorenzo; Cusumano, Davide; Boldrini, Luca; Votta, Claudio; Pollutri, Veronica; Antonelli, Marco Valerio; Chiloiro, Giuditta; Romano, Angela; De Luca, Viola; Catucci, Francesco; Indovina, Luca; Valentini, Vincenzo
Abstract: Purpose: Magnetic Resonance‐guided radiotherapy (MRgRT) systems allow continuous monitoring of therapy volumes during treatment delivery and personalized respiratory gating approaches. Treatment length may therefore be significantly affected by patient's compliance and breathing control. We quantitatively analyzed treatment process time efficiency ( TE ) using data obtained from real‐world patient treatment logs to optimize MRgRT delivery settings. Methods: Data corresponding to the first 100 patients treated with a low T hybrid MRI‐Linac system, both in free breathing (FB) and in breath hold inspiration (BHI) were collected. TE has been computed as the percentage difference of the actual single fraction's total treatment time and the predicted treatment process time, as computed by the TPS during plan optimization. Differences between the scheduled and actual treatment room occupancy time were also evaluated. Finally, possible correlations with planning, delivery and clinical parameters with TE were also investigated. Results: Nine hundred and nineteen treatment fractions were evaluated. TE difference between BHI and FB patients' groups was statistically significant and the mean TE were 42.4%, and −0.5% respectively. No correlation was found with TE for BHI and FB groups. Planning, delivering and clinical parameters classified BHI and FB groups, but no correlation with TE was found. Conclusion: The use of BHI gating technique can increase the treatment process time significantly. BHI technique could be not always an adequate delivery technique to optimize the treatment process time. Further gating techniques should be considered to improve the use of MRgRT.